Lactobacillus fermentum and Lactobacillus plantarum as Anti-inflammatory and Immunostimulant in COVID-19 Therapy: a Review - Harry Noviardi; Dyah Iswantini; Sri Mulijani; Setyanto Tri Wahyudi; Tatik Khusniati (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Covid-19 is an infectious disease caused by coronavirus and has been declared a global pandemic. The initial viral infection causes antigen-presenting cells (APC) to detect the virus through a phagocytosis mechanism in the form of macrophage and dendritic cells. Lactobacillus fermentum and Lactobacillus plantarum are Gram-positive bacteria potential to serve as immunomodulators caused by inflammation and immune system response. Short-chain fatty acids (SCFA) produced by Lactobacillus can induce immune response through tolerogenic dendritic cells. This probiotic bacterium can induce the production of different cytokines or chemokines. Following the in vitro and in vivo tests, L. fermentum and L. plantarum can induce IL-10 release to activate regulatory T-cell and inhibit tumor necrosis factor-α (TNF-α) on the binding activity of nuclear factor kappa B (NF-κB).